Correlation between the Consumption Frequency of Sugar-Sweetened Beverages with Serum Triglyceride Levels in Female Adolescents - Laga Patriantoro; Yoga Devaera; Saptawati Bardosono; Khalida Fauzia; Meirina Khoirunnisa; Dyah Saptarini (Indonesian Nutrition Association, 2019)
Background: The prevalence of overweight and obesity in adolescence increases significantly from year to year particularly in Depok. Consumption of sugar-sweetened beverages is one of the causes. Excess triglyceride levels are one of the risk factor for metabolic syndrome and cardiovascular disease. Consumption frequency of sugar-sweetened beverages is associated with increased serum triglyceride levels. Method: This study used a cross-sectional design involving 47 subjects recruited through the consecutive sampling method. The consumption frequency of sweetened soft drinks is taken by the semiquantitative FFQ method. Samples of serum triglyceride levels were taken from venous blood and measured using enzymatic methods.Result: Forty-seven subjects finished the study protocol The result showed that there is a significant positive correlation with very strong degrees (p = <0.001, r = 0.88) between the consumption frequency of sugar-sweetened beverages with serum triglyceride levels.Conclusion: There is a significant positive correlation with very strong degrees between the consumption frequency of sugar-sweetened beverages with serum triglyceride levels.Keywords: overweight, female adolescence, sugar-sweetened beverages, triglyceride